Factors Associated With Motivation of Employees Toward Training: A Case Study In Malaysia Airports Sdn. Bhd., KuchiDg International Airport. - JAYEE, TAN (Universiti Malaysia Sarawak, (UNIMAS), 2008)
The main purpose of this study is to determine rhe factors associated with motivation of employees towards training. This study was conducted in Malaysia Airport Sdn. Bhd, Kuching International Airport. There were 160 employees who were working on shift and also during normal office hour. By using a simple random sampling, a total of 130 employees from A VSEC Department (Airport Aviation Security Department) were selected as the sample of the study. A quantitative survey research was chosen to determine the relationship between the independent variables (supervisor's support, job challenge. co· worker,. institutional barriers, and situational barriers) and the dependent variable (motivation of employee towards training). The questionnaires were distributed t" the respondents to collect data. Statistical tests that \\~rc carrkd out were Pearson's Bivariate COITelation tests and Multiple Regression analysis. Pearson correlation test was used to determine the relationshir between supervisor's support (r=0.562, p<O.O I), job challenge (r=0.561 , p<O.O I). co· workers (r=0.353, p<O.O I), institutional barriers (r=·0.0 II, p>O.O I), situational barriers (r=-0.:'78, p<O.O I) and motivation of employee towards training. However, through Multiple Regression analysis, the findings also showed that th.: dominant factor that influences motivation of employee towards training was ~urervisor' s support. The findings of this study can help the management of Malaysia Airports Sd n. I~hd. , Kuching International Airport understand the factors associated with motivation of employees from AVSE Department towards training and their Current motivation level in the organization.